Effects of Dietary Soapwort Extract Supplementation on Laying Performance, Blood Biochemical Parameters, Fatty Acid Profile of Breast Meat and Antioxidative Potential of Liver and Heart Tissues in Cold Stressed Laying Japanese Quail - Ciftci, Mehmet; Dalkilic, Bestami; Simsek, Ulku Gulcihan; Azman, Mehmet Ali; Erisir, Zeki; Ozcelik, Mehtap; Bahsi, Muammer (Kafkas Univ, Veteriner Fakultesi Dergisi, 2016)
The purpose of this study was to evaluate the effects of dietary Soapwort Extract (SE) supplementation on laying performance, egg quality, some offal weights, some serum parameters, antioxidant status of liver and heart tissues and fatty acid composition of breast meat in chronic cold stressed Japanese quails. A total of sixty three 45-day-old Japanese quails were divided into three groups with three replicate. One group was fed with the corn-soybean based diet alone (control group) and the others were fed with the basal diet supplemented by 50 and 100 ppm SE. Cold stress was applied every night between 22.00 to 06.00 h as 7 +/- 1 degrees C. SE supplementation had no significant effect on laying performance, offal weights and egg quality parameters with the exception of egg and albumen weights. Serum glucose, triglyceride, uric acid and aspartate aminotransferase (AST) levels were reduced in SE-50 group. While supplementation of 100 ppm SE decreased both liver and heart MDA levels, both amounts of SE increased the liver GSH-Px enzyme activity. Supplementation of 100 ppm SE decreased the levels of oleic acid and MUFA in breast meat, and it significantly increased the linoleic, linolenic and arachidonic acid, PUFA, total omega 6 and the ratio of omega 6/omega 3. It is displayed that SE supplementation to diets of laying quails exposed to cold stress can alleviate the detrimental effects of oxidative stress with no affecting on performance parameters.
Soğuk stresine maruz bırakılan Japon bıldırcınlarında diyete ilave Edilen çöven ekstraktının yumurtlama performansı, kan biyokimyasal parametreleri, göğüs eti yağ asidi profili ile karaciğer ve kalp dokusu antioksidatif potansiyeli üzerine etkisi
Keywords: Antioxidant; Cold stress; Fatty acid; Laying performance; Saponin; Soapwort extract